On the Analytical and Numerical Solutions in the Quantum Magnetoplasmas: The Atangana Conformable Derivative (1+3)-ZK Equation with Power-Law Nonlinearity - Khater, Mostafa M. A.; Chu, Yu-Ming; Attia, Raghda A. M.; İnç, Mustafa; Lu, Dianchen (Wiley, 2020)
In this research paper, our work is connected with one of the most popular models in quantum magnetoplasma applications. The computational wave and numerical solutions of the Atangana conformable derivative (1+3)-Zakharov-Kuznetsov (ZK) equation with power-law nonlinearity are investigated via the modified Khater method and septic-B-spline scheme. This model is formulated and derived by employing the well-known reductive perturbation method. Applying the modified Khater (mK) method, septic B-spline scheme to the (1+3)-ZK equation with power-law nonlinearity after harnessing suitable wave transformation gives plentiful unprecedented ion-solitary wave solutions. Stability property is checked for our results to show their applicability for applying in the model's applications. The result solutions are constructed along with their 2D, 3D, and contour graphical configurations for clarity and exactitude.
Keywords: Traveling-Wave Solutions; Schrodingers Equation; (G'/G)-Expansion Method; Evolution; Dynamics; Solitons; Model